Body composition trends in women collegiate track-and-field athletes across two consecutive competitive seasons - McNeal, J. R.; Poole, R. C.; Sands, W. A. (The Journal of Strength and Conditioning Research, 1999)
Longitudinal body composition assessment can uncover the trends of body composition change that are indicative of high-performance track-and-field training. This descriptive study was conducted to determine body composition changes in women collegiate track-and-field athletes across 8 months of training and competition in both indoor and outdoor seasons. Body composition was estimated monthly by hydrostatic weighing from the first month of training (September) until the final month (April) for all throwers, jumpers, and sprinters. Thirty-two cases were obtained, which consisted of no less than 7 or more hydrostatic measurements. Repeated-measures analyses of variance of lean body mass (LBM), body density (BD), total body mass (TBM), percent fat (%FAT), and body mass index (BMI) revealed significant time effects for all variables. These results indicate that significant changes in body composition of women collegiate track-and-field athletes occur throughout 8 months of continuous training.